GENETIC ENGINEERING: PAST AND PRESENT - Umarova T. A.; Kudratova Z. E.; Maxmudova Z. (Web of Journals Publishing, 2025)
Genetic engineering is more than a science. It is a technological combination of different sciences: genetics, biology, chemistry, virology, chemical engineering and so on. It is a powerful tool for creating new genetic combinations, different from those existing in nature, by making changes in DNA and RNA. New genetic combinations are created in order to improve the usual set, to give a living object properties and qualities that are not inherent to it. A recombinant DNA molecule has the shape of a ring, it contains genes that constitute the object of genetic manipulation and a vector-fragment of DNA that ensures the reproduction of DNA rivers and synthesis of the final products of the genetic system activity-proteins [3,4,5].
Keywords: Genetic engineering, DNA, RNA, molecular structure, genetic combinations.